A house that once was - Fogliano, Julie (Roaring Brook Press, a division of Holtzbrinck Publishing Holdings Limited Partnership, 2018)
"Deep in the woods is a house, just a house, that once was--but now isn't--a home. Who lived in that house? Who walked down its hallways? Why did they leave it, and where did they go?"--Page [2] of cover.